The Role of the Nandi Religion in Indigenous Healthcare Management Practices among the Nandi of Kabiyet, Kenya - Karen Kogo; Simon Omare; Miriam Rono (Eastern African Journal of Humanities and Social Sciences)
Religion plays an integral role in the practice of indigenous medicine across African societies, deeply influencing healing traditions and perceptions of health. This article examines the role of religion in sustaining indigenous healthcare systems among the Nandi community of Kenya using Holism as the guiding framework. It explores how religious beliefs, practices, and institutions shape understandings of illness, healing, and well-being within a culturally embedded spiritual framework. The aim is to investigate how the Nandi religion influences traditional medical knowledge and practices. Employing a qualitative research design, data were gathered through in-depth oral interviews, participant observation, and focus group discussions. Findings reveal that Nandi religious beliefs are fundamental to the community’s health practices. Illness is often understood as a disturbance in spiritual or social order, and healing involves restoring harmony through rituals such as ancestral offerings, community cleansing, and the use of spiritually significant herbs. Religious authority legitimizes traditional healers, positioning them as key figures in maintaining both spiritual and physical health. Despite its contributions, the study faced notable limitations. Some informants were reluctant to disclose sacred knowledge, and the findings are context-specific, limiting their generalizability to other communities. The study has practical implications for the integration of indigenous spiritual frameworks into contemporary health systems. A deeper understanding of the spiritual dimensions of health can inform culturally sensitive health policies and practices. Recognizing and respecting traditional religious worldviews may foster more inclusive and holistic healthcare approaches, especially in rural and indigenous settings.